Identification of Weeds on Tea Planting (Camellia Sinensis L.) in Liki Farm Unit, PT. Mitra Kerinci, South Solok Regency - Nugraha Ramadhan; Feristika Pri Dini (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
One of the plantation products that is a mainstay export commodity and is considered quite strategic in supporting the Indonesian economy is tea. However, in recent years tea production has fluctuated, to keep Indonesia as the world's main tea producer, production problems and intensive efforts that support productivity need to be managed optimally. Tea quality is strongly influenced by environmental factors such as the presence of weeds. Assessment of the types of weeds in tea plants can be done by identification based on morphology. The purpose of this study was to identify weeds in tea plants (Camellia sinensis L.) in the Liki plantation unit at PT. Mitra Kerinci. This activity was carried out in July - August 2022 at PT. Mitra Kerinci, Sungai Lambai, Nagari Lubuk Gadang Selatan, Sangir District, South Solok Regency, West Sumatra Province. Observations were made using descriptive methods. It was concluded that there were 8 families and 14 species of broad-leaf weeds; 1 family and 2 species of Cyperaceae weeds; 1 family and 3 species of Poaceae weeds; and 3 families and 4 species of Filicinae weeds in this tea plantation.